Estimation of Andrographolide and Antioxidant Activities in Andrographis peniculata Commercial Products by Color Parameters - Petchpoung, Krittaya; Soiklom, Siriwan; Siri-Anusornsak, Wipad (Trends in Sciences, 2024)
Andrographis paniculata (Burm.f.) Wall.ex Nees is a standing out medicinal herb. It contains a large quantity of andrographolide and wildly used a traditional herb in many countries. Andrographolide is found in all part of the plant. However, those part are different in color, active compound content and antioxidant activity. Even though, there are several methods to determine andrographolide and antioxidant. They are chemical involved, complicated and time consuming. Therefore, the objective of this study was to develop estimation method of andrograhpholide content and antioxidant activities by CIE color parameters. The result showed that range of CIE color parameters of andrographolide sample were broad with range from light greyish yellow-green to greyish dark green. Antioxidant activity was barely correlated with colors. However, andrographolide content showed moderate correlation with colors. Dark green andrographis herb contain higher andrographolide than light greyish yellow-green one. Furthermore, andrographolide content could be numerical estimated by CIELab and CIELCh color parameters. The developed estimating method were easy, rapid and no chemical involved. HIGHLIGHTS Andrographolide content showed moderate correlation with colors Darker and greener andrographis herb was assumed that contain higher amount of andrographolide Andrographolide content could be numerical estimated by CIELab and CIELCh color parameters The estimating model were easy, rapid and no chemical involved GRAPHICAL ABSTRACT